Respuesta :

Answer:

(-3,1)

Step-by-step explanation:

-.6x - .5y = 1.3

.5x - .5y = -2

See the attached graph

Multiplying the second equation by -1 and adding

-.6x - .5y = 1.3

-.5x + .5y = 2

-------------------

-1.1 x = 3.3

Divide by -1.1

-1.1x/1.1 = 3.3/-1.1

x = -3

This will allow us to see if our graph makes sense

From the graph x=-3,  y=1

Ver imagen wegnerkolmp2741o
gmany

[tex]\left\{\begin{array}{ccc}-0.6x-0.5y=1.3&|\text{add 0.6x to both sides}\\0.5x-0.5y=-2&|\text{subtract 0.5x from both sides}\end{array}\right\\\\\left\{\begin{array}{ccc}-0.5y=0.6x+1.3&|\text{multiply both sides by (-2)}\\-0.5y=-0.5x-2&|\text{multiply both sides by (-2)}\end{array}\right\\\left\{\begin{array}{ccc}y=-1.2x-2.6\\y=x+4\end{array}\right[/tex]

[tex]y=-1.2x-2.6\\\\for\ x=2\to y=-1.2(2)-2.6=-2.4-2.6=-5\to(2,\ -5)\\\\for\ x=-3\to y=-1.2(-3)-2.6=3.6-2.6=1\to(-3,\ 1)\\\\y=x+4\\\\for\ x=0\to y=0+4=4\to(0,\ 4)\\\\for\ x=-4\to y=-4+4=0\to(-4,\ 0)\\\\\text{Look at the picture.}\\\\Answer:\ \boxed{(-3,\ 1)\to x=-3\ and\ y=1}[/tex]

Ver imagen gmany